An LGBTI-Inclusive Sexual History Taking Standardized Patient Case - Kristen Eckstrand; Kimberly Lomis; Lisa Rawn (Association of American Medical Colleges, 2012)
Abstract Introduction The lesbian, gay, bisexual, transgender, and intersex (LGBTI) population is disproportionately affected by providers' lack of training, particularly related to the inability to take an LGBTI-inclusive sexual history. Indeed, there is a general deficit in physician knowledge and training surrounding sexual health, including the ability to take a comprehensive sexual history. While many medical schools teach students to ask the question "Do you have sex with men, women, or both?" during a sexual history, only half of practicing physicians regularly take sexual histories, and less than a quarter elicit sexual orientation or assess for type of sexual activity. The current case evolved from an existing case featuring a heterosexual female, presenting for her Well Woman Exam, inquiring about her risk for cervical cancer. In an effort to diversify student standardized clinical experiences, the case was refined to shift the focus from cervical cancer to inclusive sexual history taking, specifically students' ability to provide quality and equitable care to the LGBTI community. Methods During the standardized patient (SP) case, students are provided a standard gynecology clinic's Well Woman's Exam template containing the question "Do you have sex with men, women, or both?" as a reference. Students are assessed on the accuracy of the clinical data they attain via an online quiz after the encounter while SPs assess students on the thoroughness of the history solicited and quality of the counseling provided using a checklist. After the encounter, students participate in a small-group debrief that addresses students' questions, discusses implicit biases, and provides LGBTI education/resources to improve knowledge and performance. Results Of 211 third-year medical students completing the SP encounter, 12.3% (n = 26) failed to ask the sexual history-taking question "Do you have sex with men, women, or both?" During debriefing, many students who failed to ask the question shared their omission and acknowledged their implicit assumptions. Of students who did elicit sexual orientation, most disclosed that they felt unprepared to provide appropriate risk-reduction counseling. Discussion Our findings demonstrate that medical students feel unprepared to perform a comprehensive sexual history inclusive of sexual and gender minorities. Targeted debriefing heightened student awareness of LGBT-specific concerns, making this a valuable exercise for students in their preparation to provide quality and equitable care to diverse populations.